LEMBAR KERJA SISWA SEBAGAI BAHAN AJAR BERBASIS PROBLEM BASED LEARNING (PBL) - Diyah Ayu Widyaningrum; Nurmala Hindun (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2020)
Student worksheet is one example of teaching material. Through LKS, students can be helped in the learning process. The resulted of observations on teaching materials in school showed that the teaching materials used still cannot accommodate an effective learning process. So it was necessary to develop teaching materials in the form of student worksheets. Developed worksheets accommodated learning models, one of them was Problem Based Learning (PBL). This type of research was a research development with the 4D model (Define, Design, Develope, and Disseminate). This research was limited to the develope stage. The number of worksheets described in this study were 2: PBL based PBL models on the XI grade motion system material of SMA Negeri 1 Kambera and PBL based PBL models on Class XI IPA Food Digestion System material. The results showed that the assessment of LKS 1 by material experts was 84%, media experts were 91%, and teachers / field practitioners were 92.5%. LKS 2 by 79.4% material experts, 86.5 media experts and 90% field teachers / practitioners. So that as a whole meets the criteria very well / very decent. Key word : student worksheet, problem based learning Abstrak. Lembar Kerja Siswa merupakan salah satu contoh bahan ajar. Melalui LKS, peserta didik dapat terbantu dalam proses pembelajaran. Hasil observasi terhadap bahan ajar yang terdapat di sekolah menunjukkan bahwa bahan ajar yang digunakan masih belum dapat mengakomodasi proses pembelajaran yang efektif, sehingga diperlukan pengembangan bahan ajar berupa LKS. LKS yang dikembangkan mengakomodasi model-model pembelajaran, salah satunya Problem Based Learning (PBL). Jenis penelitian ini merupakan penelitian pengembangan dengan model 4D (Define, Design, Develope, and Disseminate). Penelitian ini dibatasi sampai tahapan develope. Jumlah LKS yang dideskripsikan dalam penelitian ini adalah 2 buah yaitu LKS berbasis model PBL pada materi sistem gerak kelas XI SMA Negeri 1 Kambera dan LKS berbasis model PBL pada materi Sistem Pencernaan Makanan kelas XI IPA. Hasil penelitian menunjukkan bahwa penilaian LKS 1 oleh ahli materi sebesar 84%, ahli media sebesar 91%, dan guru/praktisi lapangan 92,5%. LKS 2 oleh ahli materi 79,4%, ahli media 86,5 dan guru/praktisi lapangan 90%, sehingga secara keseluruhan LKS 1 dan LKS 2 memenuhi kriteria sangat baik/sangat layak.